2020
DOI: 10.1038/s12276-020-00541-3
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents doxorubicin-induced cardiotoxicity through suppression of AMPKα2-dependent mitochondrial damage

Abstract: The clinical application of doxorubicin, one of the most effective anticancer drugs, has been limited due to its adverse effects, including cardiotoxicity. One of the hallmarks of doxorubicin-induced cytotoxicity is mitochondrial dysfunction. Despite intensive research over recent decades, there are no effective approaches for alleviating doxorubicin-induced cytotoxicity. Melatonin, a natural hormone that is primarily secreted by the pineal gland, is emerging as a promising adjuvant that protects against doxor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
(58 reference statements)
0
20
0
1
Order By: Relevance
“…It has been suggested that increased oxidative stress, such as the production of ROS, and compromise of the antioxidant system play pivotal roles in the disturbance of cardiac homeostasis in DOX-induced cardiotoxicity [ 43 , 44 ]. Mitochondria are the main sites of ROS generation and the key targets of DOX [ 45 ]. Therefore, exploring ways to inhibit oxidative stress and protect mitochondria is an attractive approach to reduce cardiac injury after DOX treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that increased oxidative stress, such as the production of ROS, and compromise of the antioxidant system play pivotal roles in the disturbance of cardiac homeostasis in DOX-induced cardiotoxicity [ 43 , 44 ]. Mitochondria are the main sites of ROS generation and the key targets of DOX [ 45 ]. Therefore, exploring ways to inhibit oxidative stress and protect mitochondria is an attractive approach to reduce cardiac injury after DOX treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in the current study, activation of AMPKα1 or maintenance of AMPKα1 levels can protect cells against cisplatin-induced toxicity. Notably, we previously reported that AMPKα2 exerts proapoptotic effects in doxorubicin-treated H9c2 cardiomyocytes by interfering with mitochondrial integrity and function and that doxorubicin induced transcription of AMPKα2 in H9c2 cells [ 20 ]. In contrast, doxorubicin inhibited the transcription of AMPKα1 in several cancer cell lines [ 15 ], observations similar to those in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…AMPKα2 is overexpressed in fibroblasts treated with doxorubicin and has been shown to activate the transcription of pro-apoptotic molecules including p27, Apaf-1, and Bim. Several studies have shown that melatonin is cardioprotective against AIC, owing to its role as a potent antioxidant and free radial scavenger (96,97). These studies also suggested that melatonin may also protect against apoptotic cardiomyocyte death, and recent data show that one of the potential mechanisms of this may be via inhibition of the upstream pathways of AMPKα2 transcription (97).…”
Section: Therapies Targeting Apoptosismentioning
confidence: 97%